Customer Satisfaction In The Malaysian Mobile Industry. A Study Using Servqual Model - Karuppiah, Nermala (2000)
This thesis deals with measurement of customer satisfaction in Mlaaysian mobile communication industry. The ability of mobile operators to focus on achieving customer satisfaction has proven to be on eof the most competitive issues toward the end of the 20th century. In this study, attention is paid to the measurement model of customer satisfaction in Malaysian's mobile phone market using the well-known SERVQUAL model developed Parasuraman, Zeithaml and Berry (PZB).